Fresh frozen cadaver workshops for advanced vascular surgical training. Issue 11 (16th August 2013) - Jansen, Shirley; Cowie, Margaret; Linehan, John; Hamdorf, Jeffery M.
Abstract Background Reduction in working hours, streamlined training schemes and increasing use of endovascular techniques has meant a reduction in operative experience for newer vascular surgical trainees, especially those exposures which are not routinely performed such as thoracoabdominal, thoracotomy and retroperitoneal aortic, for example. Methods This paper describes an Advanced Anatomy of Exposure course which was designed and convened at the Clinical Training & Evaluation Centre in Western Australia and uses fresh frozen cadavers. Feedback was obtained from the participants who attended over three courses by questionnaire. Results Feedback was strongly positive for the course meeting both its learning outcomes and personal learning objectives, and in addition, making a significant contribution to specialty skills. Most participants thought the fresh frozen cadaveric model significantly improved the learning objectives for training. Conclusions The fresh frozen cadaver is an excellent teaching model highly representative of the living open surgical scenario where advanced trainees and newly qualified consultants can improve their operative confidence and consequently patient safety in vascular surgery. An efficient fresh frozen cadaver teaching programme can benefit many health professionals simultaneously maximizing the use of donated human tissue.